Analisis Perbedaan Karakteristik Konsumen Berbagai Rasa Teh Celup Walini di Kota Bandung - Kautsar, Athhar Izzan; Deliana, Yosini (Universitas Galuh, 2024)
This study analyzes differences in consumer characteristics based on taste preferences for Walini teabags in Bandung City. Using a quantitative approach with a survey method at Borma Supermarket, Panyileukan District, samples were selected by systematic random sampling during May 2024. Data were analyzed descriptively and using cross tabulation. The results showed that Walini teabag in Wangi flavor was most preferred by 20% of respondents, with the majority of respondents being female (60%) aged 40-49 years. Preference for Wangi flavor was also dominant across employment and education categories, but in the income category, preference was split between Wangi flavor and classic black tea. These findings emphasize the importance of packaging design in influencing purchasing decisions, as well as the need for more in-depth analysis of product attributes to understand consumer preferences more comprehensively.